Menedżer czy inteligent... czyli mit anglisty w kontekstach - Nowak, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2011)
This essay discusses the image of the English scholar in Poland, using as one of its methodological tools recent developments associated with cultural studies. The irony of this approach lies in the fact that those developments have been imported to Poland by the same English scholars who are to be scrutinized in their light. Nowak locates the predicament of the contemporary English scholar between two basic positions: that of a harbinger of a foreign culture which is likely to enrich her/his native one and that of an entrepreneur who has been skilled in capitalizing on her/his knowledge and access to foreign business models. Thereby the English scholar in Poland is torn between two opposing forces which define her/him in radically different ways.